The effects of sprint interval training and detraining on aerobic fitness in young adults - Zubeyde Aslankeser; Cebrail Altinsoy (Pensar en Movimiento)
Sprint interval training (SIT) has been known to improve aerobic performance as well as health and fitness markers in non-athletic population. However, there's not enough information about performance when SIT is stopped. The aim of this study was to investigate the alterations in the detraining process of the evolution of adaptive physical fitness caused by short-term sprint interval training. The general design of the study was classified as before SIT, training period, after SIT and detraining period measurements. The subjects (n=26) completed the baseline measurements of the 20-m shuttle run test and then were randomized as training and control groups. The control group continued their daily routine and the training group ran SIT for 4 weeks. The 20-m shuttle run test was applied before and after training, and in the 4th and 8th detraining weeks. After the training period, aerobic performance increased in the training group (p<0.05). In addition, aerobic performance increases were maintained for the 4 weeks of detraining (p<0.05). But the performance increments disappeared in the 8th detraining week (p>0.05). Taking a break from the exercise program for more than 4 weeks in healthy young individuals may cause the positive effects of SIT on maximum oxygen uptake (VO2max) to disappear. SIT participants should not take a break from exercise for more than 4 weeks if they are to maintain aerobic gain.